Media discourse techniques in political interviews - Al-Azzawi, Qasim Obayes (Edelweiss Applied Science and Technology, 2025)
The study investigates a theoretical background about media discourse in general and how media affects our life and change it in a way or another, it deals specifically with the political interview and its discourse, checking for all the available techniques used in such a discourse for the purpose of mitigating face threatening acts between both the interview and interviewee. Since in most cases they (the interviewer and interviewee) are from different social states, so there is a cautious speech from both sides and still there is a persistent need for clinging to certain techniques and ways that play a crucial role in mitigating face threatening acts, seven of these techniques have been mentioned through all the research, how they are used and to what extent they are so influential in the fulfillment of the desired goals. Turn talking, turns, conversations and conversation analysis, all these subjects are shown within the theoretical side of the research. Checking of the chosen date and searching for these techniques and their importance though all the political interview are shown within a discrete section of analysis. Finally there are conclusions for their uses, effects and ratios of use to show their importance in developing the political speech and interviews.